Preparation, Characterization and Antibacterial Study of Schiff Base Derivatives - Ibrahim, Ayat Abdulkareem; Muhi, Sarah Alaa; Bandar, Dhifaf Handhal (Scientific Journal of Medical Research, 2024)
Recently developed Schiff base derivative, specifically designated as G1, was synthesized and meticulously analyzed through fourier transform infrared (FTIR) spectroscopy. Compound G1 is identified as (E)-N,1-bis(4-chlorophenyl) methenamine. The in-vitro antibacterial efficacy of these substances was thoroughly assessed in relation to Escherichia coli, Streptococcus faecalis, and Staphylococcus aureus bacterial strains. The results indicate a noteworthy antibacterial activity of compound G1, exhibiting minimum inhibition concentration (MIC) values of 16, 13, and 10 ?g/mL, respectively, when compared to the established standard.